Cancer and COVID-19 Experiences at African Cancer Centers: The Silver Lining. (2021) - Grossheim, Linda; Ruff, Paul; Ngoma, Twalib; Vanderpuye, Verna; Mwango, Gladys; Ochieng, Primus; Palmer, Dennis; Kouya, Francine; Lasebikan, Nwamaka; Ntekim, Atara; Ngoma, Mamsau; Bih, Noella; et al.
Abstract : PURPOSE: The COVID-19 pandemic significantly disrupted cancer care in Africa, further exposing major health disparities. This paper compares and contrasts the experiences of 15 clinicians in six different African cancer centers to highlight the positive aspects (silver linings) in an otherwise negative situation. METHODS: Data are from personal experience of the clinicians working at the six cancer centers blended with what is available in the literature. RESULTS: The impact of COVID-19 on cancer care appeared to vary not only across the continent but also over cancer centers. Different factors such as clinic location, services offered, available resources, and level of restrictions imposed because of COVID-19 were associated with these variations. Collectively, delays in treatment and limited access to cancer care were commonly reported in the different regions. CONCLUSION: There is a lack of data on cancer patients with COVID-19 and online COVID-19 and cancer registries for Africa. Analysis of the available data, however, suggests a higher mortality rate for cancer patients with COVID-19 compared with those without cancer. Positive or silver linings coming out of the pandemic include the adoption of hypofractionated radiation therapy and teleoncology to enhance access to care while protecting patients and staff members. Increasing collaborations using online technology with oncology health professionals across the world are also being seen as a silver lining, with valuable sharing of experiences and expertise to improve care, enhance learning, and reduce disparities. Advanced information and communication technologies are seen as vital for such collaborations and could avail efforts in dealing with the ongoing pandemic and potential future crises.